Trinidad and Tobago - Khan, Farouk (Printmaster,Trinidad and Tobago, 2011)
Description on the back of the postcard: "Quaint fishing port of San Fernando."
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fishing boats; Harbors; Cities and towns--San Fernando